Monoscopic vs. Stereoscopic Retinal Photography for Grading Diabetic Retinopathy Severity (2010)
ABSTRACT: Purpose.: To assess agreement between monoscopic and stereoscopic photography for research classification of the severity of diabetic retinopathy (DR). Methods.: Monoscopic digital (MD) images were compared with stereo digital (SD) and film (SF) photographs from a 152-eye cohort with full-spectrum Early Treatment Diabetic Retinopathy Study (ETDRS) severity levels for agreement on severity level, DR presence with ascending severity threshold, presence of DR index lesions, and repeatability of grading. Results.: There was substantial agreement classifying ETDRS DR severity levels between MD and SF (κ = 0.65, κw [linear weighted] = 0.87), MD and SD (κ = 0.66, κw = 0.87), and SD and SF (κ = 0.62, κw = 0.86) images. Marginal homogeneity analyses found no significant difference between MD and SF images (P = 0.53, Bhapkar test). The κ agreement between MD and SF ranged from 0.80 to 0.94 for the presence or absence of eight ascending DR severity thresholds. Repeatability between the readers of the MD images was equal to or better than that of the readers of SD or SF images. Severity threshold grading repeatability between readers was similar with the MD and SF images. The κ agreement between MD and SF for identifying diabetic retinopathy lesions ranged from moderate to almost perfect. The κ comparisons showed that performance of grading new vessels on the disc in MD images was slightly lower than that with the SF images. Conclusions.: Monoscopic photography can equal the reliability of stereo photography for full ETDRS DR severity scale grading.